Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4103/0972-124x.115647
|View full text |Cite
|
Sign up to set email alerts
|

Paramolar concrescence and periodontitis

Abstract: Concrescence is a developmental anomaly of dental hard tissues. It is a condition showing union of adjacent teeth by cementum. The concrescence leads to a loss of gingival architecture leading to the development of funnels, which may cause plaque accumulation thus, resulting in periodontal tissue destruction. There is a slight predilection for the mandible especially in the premolar area followed by the molar and anterior regions. Awareness of these developmental disturbances with proper diagnosis and treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…The authors continue to maintain long-term follow-up, including radiographic examination. In addition, most of the previous reports highlighted the importance of a multidisciplinary approach facilitate to the successful treatment of this dental abnormality [21,29,31,33,37,38,44,45]. The authors make a plan to cooperate with specialists, such as orthodontics, periodontics, endodontics, and prosthodontics, in multiple fields the in future if necessary.…”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…The authors continue to maintain long-term follow-up, including radiographic examination. In addition, most of the previous reports highlighted the importance of a multidisciplinary approach facilitate to the successful treatment of this dental abnormality [21,29,31,33,37,38,44,45]. The authors make a plan to cooperate with specialists, such as orthodontics, periodontics, endodontics, and prosthodontics, in multiple fields the in future if necessary.…”
Section: Prognosismentioning
confidence: 99%
“…Venugopal S, 2013 [21] To describe the presence of a concrescence between the mandibular second molar and a supernumerary tooth, with its clinical and radiographic findings…”
Section: Female 32 Mesiodistal Rctmentioning
confidence: 99%
“…Recurring inflammation of gingiva between posterior tooth [31]. Seehra et al [45], have reported Possibility of association between supernumerary teeth and macrodontia.…”
Section: S Nomentioning
confidence: 99%
“…Concrescence is most commonly observed in the posterior maxilla, often associated with an impacted third molar. However, it can occur in the mandible, between normal molars (which our second case demonstrates), a normal molar and a supernumerary molar, and in both erupted and impacted teeth. A rare case of cementum found on the enamel of an impacted wisdom tooth conjoined to the roots of an erupted second molar has been published in the literature.…”
Section: Discussionmentioning
confidence: 72%